Pengembangan Brand Awareness Pada UMKM Melalui Pelatihan Foto Produk - Esta Damaya; Putria Desti Anjani; Hisyam Efendi; Julita Dian Pramisti; Novita Ika Purnamasari (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
The development of Brand Awareness in SMEs is very influential in introducing a brand for a product. By implementing this strategy, it can make it easier for MSME actors to enter the national market with a positive image attached to the brand. The benefits of carrying out this activity are to assist in creating better content and products in an effort to develop their business. So that this activity can be used as inspiration for micro, small and medium enterprises, especially in Gunungketur Pakualaman Yogyakarta. The activity of developing the Awaness brand for MSMEs is to introduce the brand and also to attract consumers to the products being sold. The method used, namely to develop brand awareness, is a marketing method in which this method is used to remember the brand and also identify the products being sold, so that they are able to accept the knowledge we provide and apply it in their small businesses.